PET-detectable tau pathology correlates with long-term neuropsychiatric outcomes in patients with traumatic brain injury - Takahata, Keisuke; Kimura, Yasuyuki; Sahara, Naruhiko; Koga, Shunsuke; Shimada, Hitoshi; Ichise, Masanori; Saito, Fumie; Moriguchi, Sho; Kitamura, Soichiro; Kubota, Manabu; Umeda, Satoshi; Niwa, Fumitoshi; et al. (Brain (London, England : 1878), 2019)
Tau deposits is a core feature of neurodegenerative disorder following traumatic brain injury (TBI). Despite ample evidence from post-mortem studies demonstrating exposure to both mild-repetitive and severe TBIs are linked to tau depositions, associations of topology of tau lesions with late-onset psychiatric symptoms due to TBI have not been explored. To address this issue, we assessed tau deposits in long-term survivors of TBI by PET with 11C-PBB3, and evaluated those associations with late-life neuropsychiatric outcomes. PET data were acquired from 27 subjects in the chronic stage following mild-repetitive or severe TBI and 15 healthy control subjects. Among the TBI patients, 14 were diagnosed as having late-onset symptoms based on the criteria of traumatic encephalopathy syndrome. For quantification of tau burden in TBI brains, we calculated 11C-PBB3 binding capacity (cm3), which is a summed voxel value of binding potentials (BP*ND) multiplied by voxel volume. Main outcomes of the present study were differences in 11C-PBB3 binding capacity between groups, and the association of regional 11C-PBB3 binding capacity with neuropsychiatric symptoms. To confirm 11C-PBB3 binding to tau deposits in TBI brains, we conducted in vitro PBB3 fluorescence and phospho-tau antibody immunofluorescence labelling of brain sections of chronic traumatic encephalopathy obtained from the Brain Bank. Our results showed that patients with TBI had higher 11C-PBB3 binding capacities in the neocortical grey and white matter segments than healthy control subjects. Furthermore, TBI patients with traumatic encephalopathy syndrome showed higher 11C-PBB3 binding capacity in the white matter segment than those without traumatic encephalopathy syndrome, and regional assessments revealed that subgroup difference was also significant in the frontal white matter. 11C-PBB3 binding capacity in the white matter segment correlated with the severity of psychosis. In vitro assays demonstrated PBB3-positive tau inclusions at the depth of neocortical sulci, confirming 11C-PBB3 binding to tau lesions. In conclusion, increased 11C-PBB3 binding capacity is associated with late-onset neuropsychiatric symptoms following TBI, and a close correlation was found between psychosis and 11C-PBB3 binding capacity in the white matter.